Deep Search for a Scattered Light Dust Halo Around Vega with the Hubble Space Telescope - Schuyler G. Wolff; András Gáspár; George H. Rieke; Jarron M. Leisenring; Kate Su; David J. Wilner; Luca Matrà; Marie Ygouf; Nicholas P. Ballering (The Astronomical Journal)
We present a provisory scattered-light detection of the Vega debris disk using deep Hubble Space Telescope (HST) coronagraphy (PID 16666). At only 7.7 pc, Vega is immensely important in debris disk studies both for its prominence and also because it allows the highest physical resolution among all debris systems relative to temperature zones around the star. We employ the STIS coronagraph’s widest wedge position and classical reference differential imaging to achieve among the lowest surface-brightness sensitivities to date ( $\sim 4\,μ {{\rm{Jy}}\,{\rm{arcsec}}}^{-2}$ ) at wide separations using 32 orbits in Cycle 29. We detect a halo extending from the inner edge of our effective inner working angle at 10.″5 out to the photon noise floor at 30″ (80–230 au). The face-on orientation of the system and the lack of a perfectly color-matched point-spread function star have posed significant challenges to the reductions, particularly regarding artifacts from the imperfect color matching. However, we find that a halo of small dust grains provides the best explanation for the observed signal. Unlike Fomalhaut (a close twin to Vega in luminosity, distance, and age), there is no clear distinction in scattered light between the parent planetesimal belt observed with the Atacama Large Millimeter/submillimeter Array and the extended dust halo. These HST observations complement JWST GTO Cycle 1 observations of the system with NIRCam and MIRI.